1975
DOI: 10.1042/bj1500315
|View full text |Cite
|
Sign up to set email alerts
|

A study of the interrelationship between the triacylglycerol and protein components of very-low-density lipoproteins using the perfused rat liver

Abstract: High and low rates of very-low-density-lipoprotein triacylglycerol release from the perfused rat liver were achieved by using livers taken respectively from animals that had been given fructose for 48h or from animals that had been starved for 18h. 2. The higher rates of very-low-density-lipoprotein triacylglycerol release by the livers of the fructose-fed rats were associated with higher rates of very-low-density-lipoprotein protein release. 3. When the livers were perfused in the presence of [3H]leucine, rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1978
1978
1994
1994

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The mechanism(s) underlying a potent se rum triacylglycerol-lowering effect of dietary diacylglycérol is not clear at present. Reported data suggested that the hepatic secretion of triacylglycerol as a constituent of very-lowdensity lipoprotein is severely impaired in fasted rats [16,17], As the triacylglycerol-low ering effect of dietary diacylglycérol could be detected even in overnight-fasting rats (18 h of fasting) in the present study (experiment 1, 17 days of the feeding period), the alteration in hepatic lipoprotein synthesis may not ac count for the observed changes in serum triacylglycerol levels in rats fed diacylglycérol.…”
Section: Discussionmentioning
confidence: 69%
“…The mechanism(s) underlying a potent se rum triacylglycerol-lowering effect of dietary diacylglycérol is not clear at present. Reported data suggested that the hepatic secretion of triacylglycerol as a constituent of very-lowdensity lipoprotein is severely impaired in fasted rats [16,17], As the triacylglycerol-low ering effect of dietary diacylglycérol could be detected even in overnight-fasting rats (18 h of fasting) in the present study (experiment 1, 17 days of the feeding period), the alteration in hepatic lipoprotein synthesis may not ac count for the observed changes in serum triacylglycerol levels in rats fed diacylglycérol.…”
Section: Discussionmentioning
confidence: 69%
“…The maintenance diet ofthe liver donors was replaced by a fructose-rich diet. (Suri et al, 1978) 3 days before the perfusion experiments in order to increase the output of VLDlipoprotein triacylglycerol and protein (Petersburg et al, 1975).…”
Section: Animalsmentioning
confidence: 99%
“…After further centrifugation under the same conditions for 3 h, the VLD lipoproteins in the top 1.5 ml of the salt gradient were again removed and dialysed against three changes of 200 vol. of 0.9 % NaCl solution containing L-leucine (20mg/litre) to remove unincorporated [3H]leucine (Petersburg et al, 1975). VLD lipoproteins isolated as described above were then concentrated to a volume of approx.…”
Section: Liver Perfusionmentioning
confidence: 99%
See 1 more Smart Citation
“…From these previous and pre sent observations, it is supposed that the lipogenic appearance in the liver of rats fed the low protein diet would be amplified by the lipogenic nature of fructose (8-10) as a result of excess ingestion of sucrose in these rats. In the liver of normal animals, however, it is reported that the enhanced hepatic lipogenesis is associated with the higher rate of TG release from the liver (9,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 98%